Regulation of branched versus linear Arp2/3‐generated actin filaments. (20th March 2023) - Cao, Luyan; Ghasemi, Foad; Way, Michael; Jégou, Antoine; Romet‐Lemonne, Guillaume
Abstract: Activation of the Arp2/3 complex by VCA‐motif‐bearing actin nucleation‐promoting factors results in the formation of "daughter" actin filaments branching off the sides of pre‐existing "mother" filaments. Alternatively, when stimulated by SPIN90, Arp2/3 directly nucleates "linear" actin filaments. Uncovering the similarities and differences between these two mechanisms is fundamental to understanding how actin cytoskeleton dynamics are regulated. Here, analysis of individual filaments reveals that, unexpectedly, the VCA motifs of WASP, N‐WASP, and WASH destabilize existing branches, as well as SPIN90‐Arp2/3 at linear filament ends. Furthermore, branch stabilizer cortactin and destabilizer GMF each have a similar impact on SPIN90‐activated Arp2/3. However, unlike branch junctions, SPIN90‐Arp2/3 at the ends of linear filaments is not destabilized by piconewton forces and does not become less stable with time. It thus appears that linear and branched Arp2/3‐generated filaments respond similarly to the regulatory proteins we have tested, albeit with some differences, but significantly differ in their responses to aging and mechanical stress. These kinetic differences likely reflect the small conformational differences recently reported between Arp2/3 in branch junctions and linear filaments and suggest that their turnover in cells may be differently regulated. Synopsis: The Arp2/3 complex nucleates actin filaments in cells, either as branches growing off the sides of other filaments or as independent linear filaments. This study shows that the same regulatory factors can modulate the dynamics of these two types of Arp2/3‐generated filaments in vitro . The VCA motifs from branching activators WASP, N‐WASP or WASH destabilize both existing branches and Arp2/3 at the end of linear filaments. The branched actin‐destabilizing factor GMF also removes Arp2/3 from the end of linear filaments. Cortactin stabilizes Arp2/3 both at the branch junctions and at the end of linear filaments. Tensile forces and aging, which both destabilize Arp2/3 at branch junctions, have no effect on Arp2/3 at the end of linear filaments. Abstract : Linear and branched Arp2/3‐generated actin filaments respond differently to aging and mechanical stress, but are regulated in a similar manner by actin regulatory proteins in vitro .